A conserved cyclin-binding domain determines functional interplay between anaphase-promoting complex-Cdh1 and cyclin A-Cdk2 during cell cycle progression - Sorensen ,C.S; Lukas, C; Kramer, E.R; Peters, J.M; Bártek, Jiří; Lukáš, Jiří (Molecular and cellular biology, 2001)
Periodic activity of the anaphase-promoting complex (APC) ubiquitin ligase determines progression through multiple cell cycle transitions by targeting cell cycle regulators for destruction. At the G(1)/S transition, phosphorylation-dependent dissociation of the Cdh1-activating subunit inhibits the APC, allowing stabilization of proteins required for subsequent cell cycle progression. Cyclin-dependent kinases (CDKs) that initiate and maintain Cdh1 phosphorylation have been identified. However, the issue of which cyclin-CDK complexes are involved has been a matter of debate, and the mechanism of how cyclin-CDKs interact with APC subunits remains unresolved. Here we substantiate the evidence that mammalian cyclin A-Cdk2 prevents unscheduled APC reactivation during S phase by demonstrating its periodic interaction with Cdh1 at the level of endogenous proteins. Moreover, we identified a conserved cyclin-binding motif within the Cdh1 WD-40 domain and show that its disruption abolished the Cdh1-cyclin A-Cdk2 interaction, eliminated Cdh1-associated histone H1 kinase activity, and impaired Cdh1 phosphorylation by cyclin A-Cdk2 in vitro and in vivo. Overexpression of cyclin binding-deficient Cdh1 stabilized the APC-Cdh1 interaction and induced prolonged cell cycle arrest at the G(1)/S transition. Conversely, cyclin binding-deficient Cdh1 lost its capability to support APC-dependent proteolysis of cyclin A but not that of other APC substrates such as cyclin B and securin Pds1. Collectively, these data provide a mechanistic explanation for the mutual functional interplay between cyclin A-Cdk2 and APC-Cdh1 and the first evidence that Cdh1 may activate the APC by binding specific substrates.
Keywords: Animals; kinasy CDC2-CDC28; komplexy ubikvitinligas; anafáze; vazebná místa; Substrate Specificity; Ubiquitin-Protein Ligase Complexes; Fibroblasts; sekvence aminokyselin; Cell Cycle; cyklin A; lidé; Molecular Sequence Data; S Phase; anafázi podporující komplex; Protein Serine-Threonine Kinases; fibroblasty; nádorové buňky kultivované; ubikvitiny; kultivované buňky; Amino Acid Sequence; Anaphase-Promoting Complex-Cyclosome; cyklin-dependentní kinasy; Cyclin-Dependent Kinases; buněčný cyklus; CDC2-CDC28 Kinases; G1 fáze; Cells, Cultured; cyklin-dependentní kinasa 2; molekulární sekvence - údaje; Tumor Cells, Cultured; ubikvitinligasy; konzervovaná sekvence; Ligases; krysa rodu Rattus; Anaphase; G1 Phase; S fáze; Cyclin A; zvířata; Cyclin-Dependent Kinase 2; substrátová specifita; Ubiquitin-Protein Ligases; Ubiquitins; protein-serin-threoninkinasy; Rats; Conserved Sequence; ligasy; Binding Sites; Humans